Regularization of fish farming in cages in public waters in the State of São Paulo (Research, Society and Development, 2020)
The objective of this work is to analyze the efficiency of regularization processes of the net cages fish farming in federal waters of the São Paulo State, considering the cession of use at Aquaculture and Fisheries Secretary (AFS), of the Ministry of Agriculture, Livestock and Supply and the environmental licensing (EL) at Environmental Company of the State of São Paulo (ECSP). Literature review, field interviews and sectoral institutions were carried out. It was found that there is an excessive legal requirement and delay in obtaining the use cession, regardless of the size of the enterprises, as well as the EL, for medium and large ones. The regularization of the small projects, through the Declaration of Conformity for Agricultural Activity (DCAA), in the Coordination for Sustainable Rural Development, of the Secretariat of Agriculture and Supply, occurs quickly and with great adhesion. The period of processing of the use cession processes is from eight months to one year in the Navy and in the National Water Agency and up to one year at the Union Patrimony Secretariat, through the AFS. It was identified that only 24% of the projects filed with AFS (272) obtained use cession, between December 2002 and July 2020. At ECSP, between 2017 and 2020, 43 applications for environmental licensing of net cages fish farming were filed, of which 39% were approved. A total of 207 DCAAs were performed at the CDRS. Updating of legislation, integration between sectoral institutions (state and interstate) and active participation of the productive sector can contribute to the speed of regularization processes of fish farming.